To the question about rational choice between original and generic drugs: arguments to use the first - N. S. Khodzhaev; A. V. Starostina (Российский офтальмологический журнал, 2019)
Issues of safety and efficacy of drugs attracts much attention worldwide. The growing use of generics and the lack of stringent requirements to research focused on their biological and therapeutic equivalence are causing concern of ophthalmologists. The literary review presents hypotensive properties and physical characteristics of the major original and generic hypotensive eye drops.